Manajemen kegiatan siswa SMP dalam penguatan pendidikan karakter mandiri - Triyanto, Agus (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
The issue of students’ independence remains an important concern in the field of education. Schools do not only function to deliver knowledge but also play a role in shaping character through various student activities. Therefore, well-directed management of student activities becomes an important strategy to foster independent character. The purpose of this study is to understand the concept of independence according to Maria Montessori, describe activity management at SMP Al-Amanah Al-Gontory, and formulate a model for strengthening independent character based on Montessori values. The research employed a qualitative descriptive approach using interviews, observation, and documentation. Data analysis was conducted through reduction, presentation, and conclusion drawing. The findings reveal that Montessori views independence as an innate potential that needs to be facilitated through a supportive environment, practical life activities, and freedom of choice with responsibility. SMP Al-Amanah Al-Gontory has implemented POAC management (Planning, Organizing, Actuating, Controlling) in programs such as Leader of the Day, Market Day, and scouting activities. The results show improvements in students' self-regulation, responsibility, and self-confidence. This study recommends involving students in activity planning, strengthening partnerships with parents, and arranging a physical environment that supports independent exploration. Abstrak Permasalahan kemandirian peserta didik masih menjadi perhatian penting dalam dunia pendidikan. Sekolah tidak hanya berfungsi menyampaikan pengetahuan, tetapi juga membentuk karakter melalui berbagai kegiatan siswa. Karena itu, pengelolaan kegiatan peserta didik yang terarah menjadi strategi penting untuk menumbuhkan karakter mandiri. Tujuan dari penelitian ini adalah memahami konsep kemandirian menurut Maria Montessori, mendeskripsikan manajemen kegiatan di SMP Al-Amanah Al-Gontory, serta merumuskan model penguatan karakter mandiri berbasis nilai-nilai Montessori. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik wawancara, observasi, dan dokumentasi. Analisis data dilakukan melalui reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa Montessori memandang kemandirian sebagai potensi bawaan yang perlu difasilitasi melalui lingkungan yang mendukung, kegiatan kehidupan praktis, dan kebebasan memilih. SMP Al-Amanah Al-Gontory telah menerapkan manajemen POAC (perencanaan, pengorganisasian, pelaksanaan, pengawasan) dalam program seperti Leader of the Day, Market Day, dan pramuka. Temuan menunjukkan peningkatan kemampuan regulasi diri, tanggung jawab, dan kepercayaan diri siswa. Penelitian merekomendasikan pelibatan siswa dalam perencanaan kegiatan, penguatan kemitraan dengan orang tua, serta penataan lingkungan yang mendukung eksplorasi mandiri.